2016
DOI: 10.1590/s1984-82502016000400025
|View full text |Cite
|
Sign up to set email alerts
|

Internal consistency and interrater reliability of the Brazilian version of Martín-Bayarre-Grau (MBG) adherence scale

Abstract: This paper aims to analyze the measurement equivalence aspects (internal consistency and interrater reliability) of a Brazilian version of Martín-Bayarre-Grau (MBG) adherence questionnaire as part of its cross-cultural adaptation. Item-total correlation and Cronbach's alpha coefficients were used as internal consistency estimates. Stability was evaluated through test and retest comparison and expressed through intraclass correlation coefficient (ICC) and kappa with quadratic weighting. ICC for the overall scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
0
5
0
2
Order By: Relevance
“…Two asked about intentional reasons only [ 74 , 120 ] and one [ 73 ] asked about unintentional reasons only. Group-3: items asks about both the extent of, and reasons for, non-adherence [ 45 , 50 , 54 56 , 65 , 67 , 77 , 78 , 81 , 85 , 89 , 91 93 , 95 , 98 , 103 , 110 , 113 , 114 , 117 , 126 ]. Six MA-PROMs [ 50 , 54 , 81 , 92 , 93 , 98 ] in Group-3 were comprehensive enough to capture information on the extent of both medication-taking and prescription-filling and at least two additional domains from both intentional and unintentional reasons for non-adherence from the MAM framework [ 40 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two asked about intentional reasons only [ 74 , 120 ] and one [ 73 ] asked about unintentional reasons only. Group-3: items asks about both the extent of, and reasons for, non-adherence [ 45 , 50 , 54 56 , 65 , 67 , 77 , 78 , 81 , 85 , 89 , 91 93 , 95 , 98 , 103 , 110 , 113 , 114 , 117 , 126 ]. Six MA-PROMs [ 50 , 54 , 81 , 92 , 93 , 98 ] in Group-3 were comprehensive enough to capture information on the extent of both medication-taking and prescription-filling and at least two additional domains from both intentional and unintentional reasons for non-adherence from the MAM framework [ 40 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patient-reported outcome measures development was rated for the 24 original MA-PROMs [ 45 , 60 , 77 , 78 , 81 , 86 , 89 , 96 , 97 , 102 , 103 , 105 , 113 , 114 , 116 , 119 122 , 127 – 130 ] and 13 MA-PROMs [ 46 , 50 , 51 , 53 56 , 65 , 67 , 70 , 80 , 85 , 92 , 95 , 110 , 117 ] were modified versions of the original MA-PROMs. Patient-reported outcome measures development was not rated for 3 MA-PROMs [ 66 , 71 , 91 , 125 ], the development studies for two were published in a language other than English [ 71 , 91 ], and a development study could not be found for one [ 66 ]. However, all three of these original MA-PROMs were included in this review because their measurement properties had been evaluated among people with CVD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…De todas as escalas de autorrelato citadas ao longo dessa revisão, apenas o BMQ 43 , a MMAS-8 53 , a SEAMS 54 e o MBG [55][56] passaram por um processo de adaptação transcultural e validação para o português do Brasil. A seção do BMQ-específico do Beliefs about Medicines Questionnaire sofreu adaptação transcultural em Portugal 57 , apesar de ter apresentado boa consistência interna e validade de construto.…”
Section: Discussionunclassified
“…A SEAMS também é uma escala mais voltada para as barreiras voltadas à autoeficácia e à confiança do paciente e não permite a identificação do real comportamento de uso do medicamento 7 . Já o MBG, apesar de ter passado por processo de adaptação transcultural e de ter apresentado boas propriedades psicométricas [55][56] , é uma escala desenvolvida para aplicação aos usuários hipertensos, o que restringe a sua utilização.…”
Section: Discussionunclassified